2020
DOI: 10.1680/jwama.19.00041
|View full text |Cite
|
Sign up to set email alerts
|

Study of flow turbulence around a circular bridge pier in sand-mined stream channel

Abstract: Experiments were performed in a sand bed channel to investigate the effects of a mining pit on the hydrodynamics around circular bridge piers. Mean velocity profiles, Reynolds stresses, kinetic energy fluxes and scales of turbulence were analysed at critical locations along the channel bed as well as in the proximity of the pier. At the approach location where flow had passed over the pit and was approaching the pier, substantial increments in the near-bed velocities, bed shear stress and Reynolds stresses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Such cases have been reported in rivers of central Spain, Poland, England, France, and India (Chen and Liu 2009, Brestolani et al 2015, Barman et al 2017. Experimental studies have confirmed the streambed instabilities around piers as well as transverse exposure of piers, because of dredging (Yanmaz and Cicekdag 2000, Lade et al 2019a, 2019b, 2019c, Lade and Kumar 2020. Recent studies have manifested the escalation of turbulent stresses and intensities in the region of sand removal and its downstream side , Barman et al 2018.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Such cases have been reported in rivers of central Spain, Poland, England, France, and India (Chen and Liu 2009, Brestolani et al 2015, Barman et al 2017. Experimental studies have confirmed the streambed instabilities around piers as well as transverse exposure of piers, because of dredging (Yanmaz and Cicekdag 2000, Lade et al 2019a, 2019b, 2019c, Lade and Kumar 2020. Recent studies have manifested the escalation of turbulent stresses and intensities in the region of sand removal and its downstream side , Barman et al 2018.…”
Section: Introductionmentioning
confidence: 75%
“…Previously, we studied the bursting events and randomness characteristics of turbulence in the proximity of an oblong pier due to the bed excavation using the Kolmogorov complexity spectrum (Lade et al 2019a(Lade et al , 2019b(Lade et al , 2019c. We noticed that dredging causes a wider spread of complexity across the instantaneous velocity scales.…”
Section: Introductionmentioning
confidence: 99%
“…Sand extraction from riverbeds has become a thriving practice as it generates quick profit for the extracting party with low to no risk or harmful effect on the extracting party. The EIA study magnifies turbulence characteristics in the downstream flow (Barman, Kumar, & Sarma, 2018; Barman, Kumar, & Sarma, 2019a; Barman, Kumar, & Sarma, 2019b; Daneshfaraz et al, 2021; Lade, Deshpande, & Kumar, 2020; Neyshabouri, Farhadzadeh, & Amini, 2002, Padmalal & Maya, 2014). It aggravates the erosion/scouring of the river structures of interest (Lade & Kumar, 2020; Li, Wang, Ma, & Nie, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…The EIA study magnifies turbulence characteristics in the downstream flow (Barman, Kumar, & Sarma, 2018;Barman, Kumar, & Sarma, 2019a;Barman, Kumar, & Sarma, 2019b;Daneshfaraz et al, 2021;Lade, Deshpande, & Kumar, 2020;Neyshabouri, Farhadzadeh, & Amini, 2002, Padmalal & Maya, 2014. It aggravates the erosion/scouring of the river structures of interest Li, Wang, Ma, & Nie, 2020).…”
mentioning
confidence: 97%
“…Gautam channel with a straight path [18]. Lade et al (2020) examined the effect of mining pit on hydrodynamics around circular bridge piers in a laboratory channel with a straight path [19].…”
Section: Introductionmentioning
confidence: 99%